Line-Drawn Scenes Provide Sufficient Information for Discrimination of Threat and Mere Negativity. (February 2018) - Boshyan, Jasmine; Feldman Barrett, Lisa; Betz, Nicole; Adams, Reginald B.; Kveraga, Kestutis
Previous work using color photographic scenes has shown that human observers are keenly sensitive to different types of threatening and negative stimuli and reliably classify them by the presence, and spatial and temporal directions of threat. To test whether such distinctions can be extracted from impoverished visual information, we used 500 line drawings made by hand-tracing the original set of photographic scenes. Sixty participants rated the scenes on spatial and temporal dimensions of threat. Based on these ratings, trend analysis revealed five scene categories that were comparable to those identified for the matching color photographic scenes. Another 61 participants were randomly assigned to rate the valence or arousal evoked by the line drawings. The line drawings perceived to be the most negative were also perceived to be the most arousing, replicating the finding for color photographic scenes. We demonstrate here that humans are very sensitive to the spatial and temporal directions of threat even when they must extract this information from simple line drawings, and rate the line drawings very similarly to matched color photographs. The set of 500 hand-traced line-drawing scenes has been made freely available to the research community:http://www.kveragalab.org/threat.html .